PEMBERDAYAAN PETANI PORANG MELALUI PELATIHAN PENGOLAHAN UMBI PORANG PASCA PANEN - Astuti, N.M.W,; Warditiani, N.K.; Sari, P.M.N.A.; Yustiantara, P.S. (Buletin Udayana Mengabdi, 2024)
The Farmer Group "Mekar Sari Porang" has been cultivating porang since 2019. However, most porang farmers still do not know how to process porang traditionally and have not produced porang tuber products. The importance of empowering porang farmers in Dalang Village through training in making porang chips is so that it can be utilized for public health and improve the community's economy. This activity was carried out with the aim of increasing community understanding of porang and good processing for post-harvest porang tubers in the form of porang chips. The goal to be achieved from this activity is that porang farmers in Dalang Village can know and understand porang processing techniques so that later it is hoped that the community will be able to apply it in their daily lives. This activity is carried out through workshop and training. The implementation of activities starts from coordination with partners, seminars, training, and assistance in making porang chips to increase the economic value of porang. During this activity farmers are given knowledge about porang, good equipment and materials used in its manufacture, as well as good porang processing techniques such as cleaning, cutting, and drying properly. This community service activity has been successfully organized. This can be seen from the increase in posttest scores compared to the pretest scores, besides that the partners are also very enthusiastic and enthusiastic to make porang chips to be developed as an potential business. With this porang processing training, porang farmers are expected to have the knowledge and skills to process porang well and achieve higher added value to improve the welfare of porang farmers and increase the economic potential of the village.